2010
DOI: 10.2514/1.45694
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear-Aerodynamics/Nonlinear-Structure Interaction Methodology for a High-Altitude Long-Endurance Wing

Abstract: Nonlinear aeroelastic analysis is essential for high-altitude long-endurance (HALE) aircraft. In the current paper, we have presented a computational aeroelastic tool for nonlinear-aerodynamics/nonlinear-structure interaction. Specifically, a consistent nonlinear time-domain aeroelastic methodology has been integrated via tightly coupling a geometrically exact nonlinear intrinsic beam model and the generalized unsteady vortex-lattice aerodynamic model with vortex roll-up and free wake. The effects of discrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 14 publications
0
63
0
Order By: Relevance
“…Instead they observed that in general stall and other nonlinear aerodynamic effects will set in well before significant structural nonlinearity is observed. 27 Intrinsic / UVLM 164 -Murua et al 28 Displacement / UVLM 165 69 Table 3: Flutter velocity and frequency for the Goland wing at ρ ∞ = 1.02 kg m −3…”
Section: B Aeroelastic Model Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead they observed that in general stall and other nonlinear aerodynamic effects will set in well before significant structural nonlinearity is observed. 27 Intrinsic / UVLM 164 -Murua et al 28 Displacement / UVLM 165 69 Table 3: Flutter velocity and frequency for the Goland wing at ρ ∞ = 1.02 kg m −3…”
Section: B Aeroelastic Model Verificationmentioning
confidence: 99%
“…While the resulting set is not orthogonal, it was found to simplify the numerical solution of the nonlinear system. Upon projecting onto modal coordinates using (8), (1) becomes…”
Section: Intrinsic Beam Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A first-order, explicit time-stepping scheme is employed. 4,17,18 This results in a time-varying, discrete-time system of equations, written for time step k + 1, of the form…”
Section: Iia Nonlinear Flexible Aircraft Dynamicsmentioning
confidence: 99%
“…This has forced engineers to develop multi-disciplinary computational tools for early-stage and control system design that can predict the interaction of aircraft elastic response, rigid-body motion, and aerodynamic forcing. 1,2,3,4,5,6 In addition to this, several flight test programs 7,8 have been developed recently that specifically target the phenomenon of aeroelastic/rigid-body coupling with the intention of developing active aeroelastic control systems for stability augmentation and disturbance rejection. Most saliently, the intended handover of the Lockheed-developed X-56 Multi-Utility Technology Testbed (MUTT) to NASA has created a focal point for public domain research into flexible aircraft flight dynamics (FAFD) and control.…”
Section: Introductionmentioning
confidence: 99%